Alcohol interventions for LGBTQ+ adults: A systematic review. (1st August 2021) - Dimova, Elena D.; Elliott, Lawrie; Frankis, Jamie; Drabble, Laurie; Wiencierz, Stacey; Emslie, Carol
Abstract: Introduction: Gender and sexual minority populations are more likely to drink excessively compared to heterosexual and cisgender people. Existing reviews of alcohol interventions focus on specific subgroups within the lesbian, gay, bisexual, trans*, queer, questioning or otherwise gender or sexuality diverse (LGBTQ+) population and neither identify their theoretical basis nor examine how interventions are tailored to meet the needs of specific subgroups. Methods: This systematic review includes published studies reporting the effectiveness of interventions to reduce alcohol use in LGBTQ+ people. The review followed PRISMA guidelines. Quality was assessed using the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool. Results: The review includes 25 studies, with the earliest published in 2005. The majority ( n = 20) focused on men who have sex with men; only two included sexual minority women and three included trans* people. Most studies were conducted in the USA ( n = 21) and used a randomised design ( n = 15). Five studies were assessed to be of strong quality, seven moderate and 13 weak. Interventions were mainly delivered face‐to‐face ( n = 21). The most common approaches used to inform interventions were Motivational Interviewing ( n = 8) and Cognitive Behavioural Therapy ( n = 8). Nineteen studies reported a significant reduction in alcohol consumption. Discussion and Conclusions: This review suggests that for interventions to be effective in reducing alcohol consumption in LGBTQ+ people, they need to be informed by theory and adapted for the target population. Alcohol interventions that focus on sexual minority women, trans* people and people with other gender identities are needed. The findings have implications for professionals who need to identify when gender and/or sexuality are peripheral or central to alcohol use.